Reforming social welfare programs in Mongolia. (Metro Manila, Philippines Asian Development Bank, 2017)
As the lead development partner of Mongolia, ADB approved Social Welfare Support Program Phase 2 on 30 May 2017 as part of an overall IMF package to protect funding for social welfare programs for the poor and vulnerable people in Mongolia during the implementation of the extended fund facility. Phase 1 provided a systematic way to improve social welfare programs in Mongolia and established the necessary policy framework for improving targeting and consolidation of social welfare programs.
Keywords: Social rights -- Developing countries; Electronic books